ANALISIS PROSES PELAPORAN KEUANGAN PADA UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA - Dewi Oktaviani, - (2019)
This research is motivated by a problem where there is a delay in reporting the financial statements of UPN Veteran in Jakarta which have an impact on the delay of reports compiled by the Ministry of Research and Higher Education, thus influencing the delay in obtaining budget funds in the following period. In order to explore the understanding of actors from their experience directly involved in making financial reports and to uncover the process of preparing financial statements, ethnometodology is used as an approach with an interpretive paradigm. The findings obtained indicate that the cause of the delay in reporting financial statements is an internal problem that exists at UPN Veteran Jakarta. The three main parties that are the source of the causes of delay are the absence of a financial report maker section, incompatible data between BMN and SAIBA and the need for training for employees to be more competent in preparing financial statements.